(Sports) economics upside down? A comment on the Advocate General opinion in European Super League versus UEFA/FIFA - Oliver Budzinski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2023)
This comment addresses the opinion of the Advocate General (AG) of the European Court of Justice on the pending case European Super League versus UEFA/FIFA. It takes a critical perspective on selected aspects of the opinion's reasoning from a (sports) economics perspective. Highlighting the special characteristics of sports markets, the assessment of the AG Opinion raises questions such as (i) the (lack of) empirical evidence that the incumbent pursues and/or meets the legitimate objectives while the latter is still used as justifying reasons for anticompetitive conduct and arrangements (section III), (ii) the prohibitive entry barriers raised by the non-existence of a transparent and non-discriminatory authorization system preventing open competition for championships formats and organization by objective and effect (section IV), and (iii) the difficult search for a convincing theory of harm justifying the brutal enforcement of single-homing by the incumbent (section V).
Keywords: Z20; K21; L12; L40; L83; 330; European football; sports economics; antitrust; competition policy; Super League; Champions League; abuse of dominance; market power